2015
DOI: 10.1103/physrevb.92.024109
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic phase transitions inEuTi1xNbxO3

Abstract: We have investigated the structural and magnetic phase transitions in EuTi1−xNbxO3 (0 ≤ x ≤ 0.3) with synchrotron powder X-ray diffraction (XRD), resonant ultrasound spectroscopy (RUS), and magnetization measurements. Upon Nb-doping, the P m3m ↔ I4/mcm structural transition shifts to higher temperatures and the room temperature lattice parameter increases while the magnitude of the octahedral tilting decreases. In addition, Nb substitution for Ti destabilizes the antiferromagnetic ground state of the parent co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…We would like to mention that Li et al also observed similar value of the saturation moment. 13,14 The inset of the figure shows a five segment magnetization curve at 5 K without any visible hysteresis loop. To explore the nature of the magnetic transition, we have transformed the M(H) curves into the well known Belov-Arrott plots and observed a positive slope for these M 2 versus H/M (not shown) curves which indicates that the FM transition is continuous in nature.…”
Section: +mentioning
confidence: 99%
See 4 more Smart Citations
“…We would like to mention that Li et al also observed similar value of the saturation moment. 13,14 The inset of the figure shows a five segment magnetization curve at 5 K without any visible hysteresis loop. To explore the nature of the magnetic transition, we have transformed the M(H) curves into the well known Belov-Arrott plots and observed a positive slope for these M 2 versus H/M (not shown) curves which indicates that the FM transition is continuous in nature.…”
Section: +mentioning
confidence: 99%
“…27 The latter involves a fast heat exchange, i.e., the material should possess a high thermal diffusivity, which is the ratio of thermal conductivity to the thermal capacity per unit volume. From the zero-field specific heat and thermal conductivity data for the present sample and using the density 14 Another very important parameter related to the magnetocaloric effect is the adiabatic temperature change (∆T ad ), which can be calculated from the field-dependent magnetization and zero-field heat capacity data. The total entropy S(0,T) in absence of magnetic field is given by S(0,T) =  T 0 C p (0,T)/T dT and then S(H,T) may be evaluated by subtracting the corresponding ∆S m (H,T) determined using Equation (1) from this calculated value of S(0,T).…”
Section: +mentioning
confidence: 99%
See 3 more Smart Citations